Cocaine Increases Stimulated Dopamine Release more in Periadolescent than Adult Rats - Walker, Q. David (2008)
The neural mechanisms responsible for the enhanced adolescent vulnerability for initiating drug abuse are unclear. We investigated whether age differences in dopamine neurotransmission could explain cocaine’s enhanced psychomotor effects in the periadolescent rat. Electrical stimulation the medial forebrain bundle of anesthetized post-natal age 28 days (PN28) and PN65 rats elicited dopamine release in caudate nucleus and nucleus accumbens core before and after 15 mg/kg cocaine i.p. Extracellular dopamine concentrations were greater in PN65 than PN28 caudate following 20 and 60Hz stimulations and in the PN65 nucleus accumbens following 60Hz stimulations. Cocaine increased dopamine concentrations elicited by 20 Hz stimulations 3-fold in the adult, but almost 9-fold in periadolescent caudate. Dopamine release rate was lower in the periadolescent caudate although total dopamine clearance was similar to that of adults. The periadolescent caudate achieved adult levels of clearance by compensating for a lower V(max) with higher uptake affinity. Tighter regulation of extracellular dopamine by the higher uptake/release ratio in periadolescents led to greater increases after cocaine. In nucleus accumbens, dopamine release and V(max) were lower in periadolescents than adults, but uptake affinity and cocaine effects were similar. Immaturity of dopamine neurotransmission in dorsal striatum may underlie enhanced acute responses to psychostimulants in adolescent rats and suggests a mechanism for the greater vulnerability of adolescent humans to drug addiction.